The Simplex Method for Systems of Linear Inequalities - Moyer, Todd O (Ohio Journal of School Mathematics, 2017)
Abstract for The Simplex Method for Systems of Linear Inequalities This article details the application of the Simplex Method for an Algebra 2 class. In that course, students typically learn how to use the “rref” button on the graphing calculator. This leads the students to believe that every matrix can be row reduced in that manner. The Simplex Method is an example of not using the “rref” button, instead requiring students to recall the elementary row operations to be performed on matrices. Instructions on using the calculator commands are given at the end of the article.